Market Outlook and Trading System Beef Cattle in Nusa Tenggara Barat - Nyak Ilham (Indonesian Center for Animal Research and Development, 2001)
Nusa Tenggara Barat (NTB or the West Nusa Tenggara) Province is known as one of the centers of cattle production. The demand of local and national beef tend to increase. The local demand is noted still under the threshold of national standard of food sufficiency. Improvement on public welfare will subsequatly increase demandof weat. This study aimed to analyze local markets potential of beef in NTB, to analyze the contribution of NTB at national market, to analyze trading systems of cattle and beef, to assess functional relationship between the local and inter regional markets. The study was carried out in August 2000, in west Nusa Tenggara Province, using a survey method. Primary data were gathered through interviews from a number of farmers and cattle traders based on structural questionaire. Secondary data were collected from related institutions and a number of key people in NTB. Descriptive analyses were used to interpret the results. Results showed that (1) Local beef market in this area still prospective to improved. On the other hand, the involvement of NTB as a player in national market tend to be decreased. But the share quite constant and tend to be increased. (2) An efficient trading systems of cattle and beef were noticed, where farmers gained 76% of the total value paid by cattle trader and the rest was for wholesalers and retailers. (3) There was functional relationship of the local and national markets where demands for national market caused increasing the price of local market. To keep the role of this region as center of national cattle production, breakthrough efforts are needed to improve production sector by accelerating population growth and also by providing conducive circumstances in the policy to meet competitive advantage in national market. Key words: Cattle and beef, prospect, marketing, NTB